Implementation of STEM learning technology in the process of calibrating an NTC thermistor and developing an electronic thermometer based on it - Roman P. Kukharchuk; Tetiana A. Vakaliuk; Oksana V. Zaika; Andrii V. Riabko; Mykhailo G. Medvediev (Academy of Cognitive and Natural Sciences, 2023)
The rapid development of information technology, robotics, nanotechnology, and biotechnology requires modern education to train highly qualified specialists who can support it, preparing students and students for producing creative work. The need to reform education to modern challenges is an urgent problem today. It is predicted that the most popular professions soon will be programmers, engineers, roboticists, nanotechnologists, biotechnologists, IT specialists, etc. STEM education can combine these areas into a complex, which can be implemented in different age groups. One example of the use of STEM technologies is the development and implementation of scientific and technical projects using the Arduino hardware and software complex. With the help of STEM technologies, a method for calibrating an NTC thermistor in the operating temperature range is proposed and a working model of an electronic thermometer is presented using the example of an NTC thermistor and an Arduino microcontroller.